Bridge Employment Model of Qualified Employees in Iran's Public Organizations - Seyedeh Sanaz Sadafi Mousavi; Mir ali Syed nagavi; Seyed Mehdi Alvani; Alireza Koushki Jahromi (پژوهش‌های مدیریت عمومی)
Abstract One of the characteristics of today's age is the increase in the age of specialized employees and, as a result, the decrease in the number of these forces, therefore, the aging and shrinking of the workforce is a big challenge for organizations and governments. On the other hand, increasing the age and the aging process of the population, improving life expectancy, reducing the number of births and the economic and social situation of the society, the desire of retired employees to return to the labor market has increased and it is necessary to address the conditions and expectations of this working group in the society. to be Employment after retirement from regular full-time jobs and before complete withdrawal from income-generating activities is known as bridge employment. This research was carried out with the aim of investigating the employment pattern of experts in Iran. This research is qualitative, developmental, interpretive and inductive, which was implemented with the foundation's data approach. The statistical population of the research consists of ten academic-executive experts who are currently employed in the bridge and were selected by a judgmental method. After selecting the statistical population, the research questions were answered through semi-structured interviews. After reviewing and analyzing the obtained interviews, 186 initial codes were obtained, of which 76 abstract concepts, 22 subcategories, and 15 main categories were obtained. In this way, the factors; environmental, social, individual, psychological and governmental as causal conditions; The legal requirements of the value system governing Paul's employment as background factors; Organizational and situational factors were identified as intervening factors, government action, organization action and human resource management department action as strategy, organizational-knowledge, infrastructural-cost, individual-motivational factors were identified as the consequences of Paul's employment. The presented model can be a basis for planning organizations to reuse the experiences, knowledge, expertise and skills of retirees in professional and non-professional jobs. It should be mentioned that the prerequisite for the correct implementation of Paul's employment in governmental and non-governmental organizations of the country is the formulation and implementation of appropriate human resources policies and strategies.Introduction Population aging is a global demographic trend, and developed countries are preparing to take advantage of its most positive effects. Population aging can even be beneficial if countries can meaningfully engage with older people. Employment after retirement from regular full-time jobs and before complete withdrawal from income-generating activities is known as bridge employment, which is divided into two types: professional bridge employment and non-professional bridge employment.Case study The case study of the present research is to present the bridge employment model of expert employees in Iranian government organizations from the perspective of experts active in bridge employment as opinion leaders in this field.Materials and Methods This research is qualitative, developmental, interpretive and inductive, which was implemented with the foundation's data approach. The statistical population of the study consists of ten academic-executive experts who are currently employed as bridge workers and were selected through a judgmental method. After selecting the participants, the research questions were answered through semi-structured interviews.Discussion and Results After reviewing and analyzing the obtained interviews, 186 initial codes were obtained, of which 76 abstract concepts, 22 subcategories, and 15 main categories were obtained. In this way, the factors; environmental, social, individual, psychological and governmental as causal conditions; The legal requirements of the value system governing Paul's employment as background factors; Organizational and situational factors were identified as intervening factors, government action, organization action and human resource management department action as strategy, organizational-knowledge, infrastructural-cost, individual-motivational factors were identified as the consequences of Paul's employment.ConclusionPreviously, Iranian society was considered a young society, but recent demographic studies have shown that Iranian society is moving towards an aging society. Therefore, the characteristics of work in this society have become important, the most important of which is retirement, which has advantages (for example, deeper thinking about the meaning and significance of life) and disadvantages (for example, financial pressure and fatigue symptoms).Just as part of a person’s life is his job, retirement is also a part of his life. Just as research is conducted to optimize a person’s working life, it is essential to think and research about the stage after his working life so that the retirement stage is not considered an abnormal stage and does not cause a loss of balance in the individual’s life. For nearly thirty years, retirement has been discussed not as a momentary event but as a process. The presented model can be a basis for planning organizations to reuse the experiences, knowledge, expertise and skills of retirees in professional and non-professional jobs. It should be mentioned that the prerequisite for the correct implementation of Paul's employment in governmental and non-governmental organizations of the country is the formulation and implementation of appropriate human resources policies and strategies.